(untitled) (Jurnal Bahasa, 2022)
This study focuses on the application of syntactic analysis in the aspect of sentence building in children’s fiction essays by slow learner students in primary school in Selangor and Putrajaya, Malaysia. The objectives of this study are: to analyze the structure of syntactic elements produced in children’s fiction essays by a selected sample; to associate the structure analysis of the syntactic elements with the ability of the study sample in the writing of children’s fiction essays from a language point of view; as well as to recommend teaching and learning (PdP) strategies in the aspect of writing for slow learner students. The syntactic aspect selected for the analysis of this study is the build-up of the sentence, which includes a single sentence, a combined compound sentence, a plural sentence of spikes and a mixed compound sentence. The construction aspect of a sentence is a basic aspect of syntax that needs to be mastered in order to convey information. The syntactic analysis model used is a model highlighted by Awang (2015), which is an adaptation of the Short and Leech Models (1981, 2007) in the fictional prose analysis method. From the analysis, it was found that the sample of this study consists of slow learner students who are able to apply syntactic analysis to produce sentences in syntactic hierarchies, from single sentences (the simplest sentences) to more complex sentences (combined compound sentences and spike compound sentences). Keywords: Syntactic analysis, sentence building, fiction essay, slow learner students, writing, children Full text: PDF